Konsentrasi dan Persepsi Kinestetik sebagai Penentu Keterampilan Bermain Futsal - Henri Gunawan Pratama; Ahmad Galum Fathur Rahman; Muhammad Muhyi; Suharti Suharti; Fakhrur Rozy (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. This study aims to examine the role of concentration and kinesthetic perception as determinants of futsal playing skills among extracurricular players. Materials and methods. This study employed a correlational research design with a survey approach. The participants consisted of 20 extracurricular futsal players selected through purposive sampling. Data were collected using the Concentration Grid Test (CGT) for concentration, the Vertical Linear Space Test for kinesthetic perception, and a standardized futsal playing skills test. Data were analyzed using multiple regression analysis with SPSS. Results. The results showed that concentration had a significant effect on futsal playing skills (t = -3.725, p = 0.002), indicating its important role as a cognitive factor in performance. In contrast, kinesthetic perception did not show a significant partial effect (t = 0.400, p = 0.694). However, the simultaneous test revealed that concentration and kinesthetic perception jointly had a significant effect on playing skills (F = 8.033, p = 0.003), suggesting a combined contribution of cognitive and sensorimotor aspects. Conclusions. Concentration plays a dominant role as a cognitive determinant of futsal performance, while kinesthetic perception acts as a complementary factor. These findings emphasize the importance of integrating psychological and sensorimotor training to improve futsal performance. However, given the relatively small sample size and the focus on a single extracurricular futsal setting, the findings should be interpreted with caution and may not be generalized to broader futsal populations.